ANALISIS FATWA NO:77/DSN-MUI/V/2010 TERHADAP MARAKNYA KREDIT DAN INVESTASI EMAS BERDASARKAN TINJAUAN ‘URF - Muhammad Izzul Fahmi; Abdul Fattah (Universitas Kiai Abdullah Faqih Gresik, 2024)
Abstract: In this modern era, gold investment has become a popular choice in Indonesia, as shown by the Katadata Insight Center survey which stated that 58.5% of respondents chose gold as their main form of investment. In line with technological developments and ease of transactions, cashless gold buying and selling is becoming increasingly common, including in the form of sharia products offered by financial institutions such as Bank Syariah Indonesia and Pegadaian Syariah. However, this transaction caused controversy from an Islamic legal perspective, considering that gold is a usurious commodity that must be traded in cash. This research uses a qualitative literature study method with secondary data from literature and the MUI website. Stages include data collection, fatwa analysis, and drawing up conclusions. The focus of this research is to examine the concept of DSN MUI fatwa no. 77/DSN-MUI/V/2010 concerning non-cash buying and selling of gold and analyzing the legal basis based on 'urf. This fatwa was born based on the principle of legal istinbath which takes into account the Al-Qur'an, hadith, ushul fiqh rules, and relevant fiqh rules, especially those related to the concept of 'urf (tradition). However, this fatwa is still a matter of debate among ulama because of the potential for usury, speculation and gharar in non-cash gold buying and selling transactions. In this way, it is hoped that it can provide a more comprehensive understanding of the legal validity of these transactions in the context of sharia economics in Indonesia. Keywords: Gold Investment, Cashless buying and selling, MUI DSN Fatwa, 'Urf.